Комерційна таємниця: захист, правові аспекти її використання та вплив на економіку підприємств в Україні - Блага, Вікторія Вікторівна; Шевердіна, Алла Володимирівна; Благой, Віталій Валерійович (НТУ "ХПІ", 2015)
Актуальність дослідження обумовлена відсутністю чіткого механізму правового захисту та економічного регулювання такого поняття як комерційна таємниця. В статті позначені межі існуючого законодавства щодо регулювання захисту комерційної таємниці та відпові дальності за її розголошення. Предметом дослідження є правові аспекти захисту комерційної таємниці на підприємствах в Україні. Метою дослідження є визначення механізмів становлення інформації про підприємство комерційною таємницею. Результати: проведено дослідження законодавства, що стосується інформаційної безпеки в Україні.

Relevance of this study is due to the absence of a clear mechanism of legal protection and economic regulation of such thing as a commercial secrecy. The article marked boundaries of existing law to regulate the protection of commercial secrecy and responsibility for its disclosure. The subject of study is the legal aspects of the protection of commercial secrecy in enterprises in Ukraine. The aim of the study is to determine the mechanisms of formation of business information commercial secrecy. Results: legislationstudied relating to information security in Ukraine. Existing today in Ukraine contradictions in the regulations on the definition of commercial secrecy may be removing only if and adoption – the Law of Ukraine "On commercial secrecy" that would regulate the legal status and ways of protection the right of commercial secrecy or based on making changes in the existing legislation provisions. However, the second option is quite complex because users need to simultaneously use a number of legislative acts that usually have conflict and bear ambiguous interpretation of the fundamental relationships. To improve the effectiveness of the legal protection of commercial secrecy should be agencies to provide activities at the national level to provide services to enterprises to develop the system of legal protection of information, consulting companies and entities of economic activity on these issues would prepare specialists in the protection of commercial secrecy. Becoming same system of economic security or organization should take place under conditions agreed with the government's economic policy directions and measures to ensure the economic protection of business entities.
Tradesecret: protection, legal aspects of its use and impact on the economy of enterprises in Ukraine
Keywords: власність інтелектуальна; захист інформації; безпека економічна; intelligent property; commercial activity; protection of information